Cryptococcal Meningitis among AIDS Patients in Jakarta - Ridhawati Sjam; Mulyati; Robiatul Adawiyah; Darma Imran; Retno Wahyuningsih (Fakultas Kedokteran Universitas Kristen Indonesia, 2012)
Abstract Cryptococcosis is a common opportunistics infections in AIDS and caused by the encapsulated yeast Cryptococcus neoformans. The predominant clinical manifestation in AIDS patients is meningitis. For the establishment of diagnosis, India ink test and culture were done. Serology test to detect capsular antigen glucoronoxylomannan (GXM) was done to support the diagnosis of cryptococcosis. The aim of this study is to know the prevalence of cryptococcosis among AIDS patients with CNS involvement in Jakarta and its surrounding places. The study was conducted from 2005 – 2007 at the Mycology laboratory Department of Parasitology, University of Indonesia, Faculty of Medicine. Spinal fluid from 154 AIDS patients with CNS involvement from Cipto Mangunkusumo hospital and other hospitals around Jakarta were tested using India ink test and cultured on sabouraud dextrose agar (SDA) and bird seed agar (BSA) and 48 were tested by latex agglutination test to detect GXM antigen. Out of 154 spinal fluids tested by india ink and culture, 32 (20,77%) samples contained Cryptococcus. GXM antigen was detected in 29 out of 48 samples. From 29 samples with GXM antigen, eight samples were also positive after mycology examination. The prevalence of cryptococcosis among AIDS patients with CNS involvement in Jakarta is 20.77%. Key words: spinal fluid, Cryptococcus neformans, prevalence, GXM antigen Abstrak Kriptokokosis yang disebabkan oleh khamir Cryptococcus neoformans merupakan infeksi oportunistik pada AIDS, dan meningitis adalah manifestasi klinis yang paling sering ditemukan. Untuk menegakkan diagnosis digunakan pemeriksaan tinta India dan kultur pada media agar. Uji serologi untuk deteksi antigen kapsular glucoronoxylomannan (GXM) dapat digunakan untuk mendukung penegakan diagnosis. Penelitian ini bertujuan untuk mengetahui prevalensi kriptokokosis pada penderita AIDS dengan gangguan serebral yang dilaksanakan sepanjang April 2005 – February 2007. Sebanyak 154 cairan otak penderita AIDS dari daerah Jakarta dan sekitarnya diperiksa dengan sediaan tinta India, dan kultur pada agar sabouraud dekstrose (ASD) dan bird seed agar (BSA). Dari 154 sampel, hanya 48 sampel yang menjalani pemeriksaan antigen GXM dengan metode agglutinasi lateks. Dari 154 cairan otak yang diperiksa dengan tinta india dan kultur 21 (20,77%) sampel mengandung Cryptococcus. Antigen GXM terdeteksi pada 29 dari 48 sampel. Dari 29 sampel yang positif antigen GXM, delapan positif mengandung Cryptococcus. Prevalensi kriptokokosis pada penderita AIDS dengan gangguan SSP di Jakarta sebesar 20,77%. Kata kunci: cairan otak, Cryptococcus neformans, prevalensi, antigen GXM